2012
DOI: 10.1063/1.3699973
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoretic differentiation of mouse ovarian surface epithelial cells, macrophages, and fibroblasts using contactless dielectrophoresis

Abstract: Ovarian cancer is the leading cause of death from gynecological malignancies in women. The primary challenge is the detection of the cancer at an early stage, since this drastically increases the survival rate. In this study we investigated the dielectrophoretic responses of progressive stages of mouse ovarian surface epithelial (MOSE) cells, as well as mouse fibroblast and macrophage cell lines, utilizing contactless dielectrophoresis (cDEP). cDEP is a relatively new cell manipulation technique that has addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 55 publications
(84 reference statements)
4
59
0
Order By: Relevance
“…4 Addressing the challenge of isolating ovarian cancer cells from peritoneal fluid, we previously demonstrated that a microfluidic approach based on exploitation of cell electrical properties could be useful. 30 We reported that MOSE cell stages ranging from benign to malignant undergo complete trapping at different voltages in the frequency range of 200-600 kHz. 30 The current paper expands the work from our previous study by further investigating the differences in the electrical properties of each cell stage of the MOSE model.…”
Section: -13mentioning
confidence: 99%
“…4 Addressing the challenge of isolating ovarian cancer cells from peritoneal fluid, we previously demonstrated that a microfluidic approach based on exploitation of cell electrical properties could be useful. 30 We reported that MOSE cell stages ranging from benign to malignant undergo complete trapping at different voltages in the frequency range of 200-600 kHz. 30 The current paper expands the work from our previous study by further investigating the differences in the electrical properties of each cell stage of the MOSE model.…”
Section: -13mentioning
confidence: 99%
“…22 Contactless DEP microfluidic device was utilized to study the behavior of mouse ovarian cells. 23 Human cervical carcinoma cell line HeLa was concentrated using circular microelectrodes. 24 DEP-based printed circuit boards have been used for software controlled entrapment and movement of human tumor cells.…”
mentioning
confidence: 99%
“…The presented technique has been successfully used for a variety of more complex and physiologically relevant applications, including sorting live and dead cells, 28 tumor initiating cells from prostate cancer cells, 30 cancer cells from dilute red blood cells, 31,32 and differentiating among stages of breast cancer 37 and ovarian cancer. 29 cDEP has also been used for mixing particles. 38 These applications suggest that by using the simple technique presented, diverse purposes can be accomplished simply by altering the design of the channel geometry.…”
Section: 36mentioning
confidence: 99%
“…Higher frequency devices (100-600 kHz) have operated using pDEP and achieved batch sorting of cells, such as prostate tumor initiating cells (TICs), murine ovarian surface epithelial (MOSE) cells, MDA-MB-231 breast cancer cells, or live THP-1 cells by selectively trapping cells of interest on insulating posts located in the sample channel. [28][29][30][31] Lower frequency (5-100 kHz) devices operate continuously, and when operated at a frequency at which one population experiences pDEP while the background population experiences nDEP, can redirect particle trajectories to achieve sorting. [32][33][34] These low frequency devices have been used to sort cancer cells from red blood cells, determine the changes in dielectric properties of a progressive MOSE cell line, and to elucidate the effects of non-toxic sphingolipid treatments on reversing aggressive characteristics of aggressive MOSE cells.…”
Section: Introductionmentioning
confidence: 99%